2020
DOI: 10.1155/2020/8866680
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Failure and Fracture Mechanism of Sandstone under Hydraulic-Mechanical Coupling

Abstract: Hydraulic coupling often leads to progressive rock failure accidents. Mechanical tests were performed over a range of combined pore water pressure and confining pressure stress path conditions to study the progressive failure characteristics of sandstone under hydraulic-mechanical coupling and explore the crack initiation and pore water fracture mechanism. The closure stress and damage stress were determined by the axial deformation stiffness and volume deformation stiffness. The experimental results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…It can be observed that all of the tested values of adhesion pressure fall in the range between 3000 and 6000 psi. This range agrees with most of the experimental failure tests on a large number of sandstones, 40 42 corroborating the applicability of MD simulations as a useful and predicting tool for studying the failure of sandstone rocks.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It can be observed that all of the tested values of adhesion pressure fall in the range between 3000 and 6000 psi. This range agrees with most of the experimental failure tests on a large number of sandstones, 40 42 corroborating the applicability of MD simulations as a useful and predicting tool for studying the failure of sandstone rocks.…”
Section: Resultssupporting
confidence: 81%
“…The resulting surface free energy and cohesive pressure are shown in Table . It was found that the resulting cohesion pressures of the cement and the silanol surfaces fall in the range of a mechanical failure of sandstones indicating a possible representation of mechanical failure in sandstones. …”
Section: Resultsmentioning
confidence: 99%